Kajian hukum terhadap peraturan daerah Kabupaten Malang yang berkaitan dengan peningkatan penanaman modal - Laila, Khotbatul (Jurnal Cakrawala Hukum, 2020)
One indicator of the success of efforts to increase economic growth and investment attractiveness is the number of investment activities that exist. Therefore, as an area characterized by cities, investment becomes a very important thing for economic growth in Malang Regency. Investment activities are more focused on efforts to utilize local potentials and increase institutional capacity and develop various investment alternatives. Therefore, the private sector and the community need to be encouraged and improved to develop their businesses, including making choices for development activities. Therefore, the research entitled "Legal Review of Malang Regency Regulations Related to Increasing Investment" in Malang Regency is important as one of the efforts of researchers to participate in helping to improve development in Malang Regency in terms of improving regulations and local regulations. How to cite item:Â Laila, K. (2020). Kajian hukum terhadap peraturan daerah Kabupaten Malang yang berkaitan dengan peningkatan penanaman modal.Â Jurnal Cakrawala Hukum, 11(1), 82-90. doi:https://doi.org/10.26905/idjch.v11i1.4118